Gender moderates the association between resting vagally mediated heart rate variability and attentional control - Zhang, Xiaocong; Wang, Siyu; Sun, Yueyi; Ding, Yanwen (Frontiers in Psychiatry, 2023)
Background: Women typically exhibit weaker attentional control ability than men. Lower resting vagally mediated heart rate variability (vmHRV) is thought to reflect the poorer function of the neurophysiological pathways underlying attentional control and thus, poorer attentional control ability. However, existing findings are inconsistent regarding the relationship between vmHRV and attentional control. Gender may be an important moderator.Objective: To examine whether gender moderates the relationship between resting vmHRV and attentional control, and to provide neurophysiological evidence for elucidating gender differences in attentional control ability.Methods: Two hundred and twenty college students completed the Attentional Control Scale to evaluate their attentional control ability. Resting vmHRV was assessed during a 5-min baseline period using an electrocardiographic amplifier (ECG100C) of the Biopac MP150 physiological recorder.(1) There was no significant difference in the total scores of the Attentional Control Scale between men and women (t=0.498, p> 0.05), but the scores of the attentional shifting dimension of women were significantly lower than those of men (t= 1.995, p< 0.05); (2) Resting vmHRV was significantly negatively correlated with attentional control in women(r= -0.233, p< 0.01), whereas the correlation was not significant in men; (3) Gender significantly moderated the relationship between resting vmHRV and attentional control (B= -3.088, 95% boot CI [-5.431, -0.745], t= -2.598, p< 0.05); (4) Among participants with lower resting vmHRV, there was no significant difference in attentional control between men and women (B= 2.284, 95% boot CI [-0.748, 5.310], p> 0.05), but among participants with higher resting vmHRV, men scored significantly higher than women in attentional control (B= -3.377, 95% boot CI [-6.406, -0.348], p< 0.05).Gender moderates the relationship between resting vmHRV and attentional control, with higher resting vmHRV in women reflecting a compensatory response to deficits in attentional control.